White and orange fleshed-sweet potato starches modified by autoclave (Research, Society and Development, 2021)
.The objective of this research, using a Composite Central Rotational Design, was to evaluate whether the moisture and exposure time to a temperature of 121 °C and pressure of 1.1 kgf. cm2 in an autoclave would be capable of modifying the morphological, thermal, functional and pasting properties of orange (OSP) and white (WSP)-fleshed sweet potato starches. The modification increased: the WAI at 60ºC of WSP starch and of WSI at 60ºC of OSP starch, the setback of WSP starch, the final viscosity of OSP starch and enthalpy for both, besides reduced the breakdown of OSP starch. The micrographs of modified starches showed cracks and on the surface of the granules, and pre-gelatinization of OSP starch, confirming that the moisture and exposure time affected their morphological, thermal, functional and pasting properties. Therefore, due the promising use the authors suggest future researches with WSP and OSP autoclaved starches to test technological applications.